Does a Wife's Bargaining Power Provide More Micronutrients to Females : Evidence from Rural Bangladesh - Rahman, Aminur (World Bank, Washington, DC, 2013)
Using calories in a unitary framework, previous literature has claimed lack of gender inequality in intrahousehold food distribution. This paper finds that while there is lack of gender disparity in the calorie adequacy ratio, the disparity is prominent among children, adolescents, and adults for a number of critical nutrients. Pregnant and lactating women also receive much less of most of these nutrients compared with their requirements. A wife's bargaining power (proxied by assets at marriage), as opposed to her husband's, significantly and positively affects the nutrient allocations of children and adolescents and of adult females. The bargaining effects remain significant after controlling for unobserved household characteristics and the potential nutrition-health-labor market linkage. The findings, which have important policy implications for the growing problem of micronutrient malnutrition in the developing world, also imply that perhaps the nutrition-health-labor market linkage as a key explanation for intrahousehold food distribution has been overemphasized in the previous literature.